Studi Deskriptif Kepuasan Pasien BPJS terhadap Mutu Pelayanan TPPRJ di Rumah Sakit Bhayangkara TK III Banjarmasin - Husin Husin; Noortuty Awaliah Awaliah (Jurnal Kesehatan Indonesia, 2020)
Hospital’s services depending on the service’s quality. Professional service on registration in the hospital can be arranged through the ability of officers in providing information, the speed and timeliness of service, responsiveness and reliability. This research aims to know the description of patient satisfaction BPJS on quality of service TPPRJ in hospital Bhayangkara Tk.III Banjarmasin. The research method used is descriptive. The population of this research are all patients BPJS who came for the medication to the registration site outpatients with a population of 1085 patients in January – March 2018. The sampling techniques used in this research was simple random sampling as much as 97 sample. The technique analysis of univariate data. The research results obtained largely satisfied as much as 62 people, as many as 44 tangibles dimension of satisfied people, dimensions Reability satisfied as much as 49 people, the dimension of Responsiveness is satisfied as much as 55 people, dimensions Assurance satisfied as much as 51 people, dimensions Emphaty satisfied as many as 49 people